Modeling crop water stress index (cwsi) in tree seedlings - Sneha C (Department of Tree Physiology and Breeding,College of Forestry, 2011)
The research work on 'Modeling crop water stress index (CWSl) in tree seedlings' was taken up at Department of Tree Physiology and Breeding, College of Forestry during April 2010 to March 2011. The objective of the study was to detect water stress in seedlings of teak and mahogany with the help of infrared thermometry by developing CWSI. Six month old seedlings were provided with four different irrigation treatments- irrigation at lW/ET=l, 0.6 and 0.3 on weekly interval and a control treatment was maintained with no irrigation (IWIET=O). Plant canopy temperature was recorded on daily basis from each treatment using a hand held infrared therinometer (HTC lR-8811). The non-water-stressed baseline (NWSB), obtained from canopy air temperature deficit and vapour pressure deficit (VPD) in the well watered treatment (irrigation at 1.0 lW/ET) and water stressed baseline obtained from non irrigated lW/ET=O. For teak the lower baseline was determined as CATD = -1.01VPD+2.8 and the upper baseline equation was CATD = -O.OSVPD+S.1. For mahogany, lower baseline equation was CATD = -0.2SVPD-2.9 and the upper baseline equation was CATD = -0.01 VPD+6.1. CWSl was calculated for each treatment using these baseline equations. The CWSl responded to irrigation events along the whole season, and clearly detected mild water stress, suggesting extreme sensitivity to variations in plant water status. Non irrigated lW IET=O showed a greater value for CWSl for all the time followed by treatment provided with irrigation at lW IET=O.3 while the treatments with higher irrigation levels (IWIET= 1 and 0.6) had lower CWSl values. It indicates that there is an increase in CWSl with time as available water in the soil decreased. It has been observed during the study that teak seedlings are more susceptible to water stress than mahogany. Observation on canopy air temperature deficit showed that, teak seedlings from all treatments maintained a constant canopy air temperature deficit all over the week. In mahogany, lWIET=l and lWIET=O maintained a constant canopy air temperature deficit, whereas, lW/ET=0.6 and lW/ET=0.3 showed a slow increase